Design Strategy 2D Animation Infographic to Raise Awareness of Indonesian Games - Ketut Adhi Apriana; Anggraeni Kurnianing Tyas; Rizkita Ayu Mutiarani; I Wayan Sunarya; I Nyoman Widhi Adnyana (Jurnal Ekspresi : Desain Komunikasi Visual dan Seni, 2025)
The Indonesian gaming industry has experienced rapid growth, yet locally developed games struggle to gain significant visibility and market share. This issue is primarily due to ineffective promotional media, low public awareness, and limited marketing budgets among local game developers. Without strong visual communication strategies, Indonesian games find it difficult to compete with foreign products that have broader access to digital marketing platforms and global gaming communities. This study aims to develop a 2D animated infographic as a promotional medium to enhance public awareness of Indonesian-made games. The research follows a three-stage design process: pre-production, production, and post-production, with a futuristic and cyberpunk visual approach to appeal to young gamers. The study results demonstrate that strong visual strategies, dynamic animation, and engaging storytelling can significantly improve audience engagement and the effectiveness of promotional media. The findings suggest that 2D animated infographics can be a powerful tool in increasing the visibility of local games, thus contributing to the growth of Indonesia’s gaming industry.